(untitled) (Indian Journal of Child Health, 2020)
Macrophage activation syndrome (MAS) is a life-threatening complication of systemic-onset juvenile idiopathic arthritis (sJIA) marked by the sudden onset of non-remitting high-grade fever, lymphadenopathy, hepatosplenomegaly, and profound depression in all three blood cell lines and elevated serum liver enzyme levels. Although MAS can occur in any systemic rheumatological disorder, it is most common in sJIA. In children with sJIA, the clinical picture may mimic sepsis or an exacerbation of the underlying disease. Early and aggressive immunosuppression is likely to benefit these patients. Hereby, we report a case of a 6-year-old male patient who presented with high-grade fever, joint pain, and rashes and was diagnosed as systemic-onset juvenile idiopathic arthritis with MAS.